Evaluation of novel protease inhibitors against darunavir‐resistant variants of HIV type 1. Issue 1 (24th November 2016) - Inoue, Mari; Oyama, Daiki; Hidaka, Koushi; Kameoka, Masanori
Abstract : HIV disease became a manageable chronic disease since combination antiretroviral therapy (cART) was introduced as the standard treatment regimen. However, the emergence of drug‐resistant viruses is a major problem associated with cART. A phenotypic drug susceptibility test using a lentiviral vector was established and applied to evaluate new protease inhibitors (PIs). Lentiviral vectors representing a wild‐type (WT‐lentivector) and darunavir (DRV)‐resistant HIV type 1 (HIV‐1) (DRV r ‐lentivector) were generated. Nine clinically approved protease inhibitors (PIs) inhibited the transduction ability of WT‐lentivector similar to their inhibitory effects on the replication of WT HIV‐1. Three new PIs reduced the transduction ability of WT‐ and DRV r ‐lentivector, suggesting that these PIs may be the candidates as novel antiretroviral drugs against drug‐resistant variants of HIV‐1. Abstract : A HIV‐1 phenotypic drug susceptibility test that can be conducted in a biosafety level 2 laboratory was established by using a lentiviral vector system. Three new protease inhibitors (PIs), KNI‐1657, KNI‐1715 and KNI‐5003 strongly reduced the transduction ability of darunavir‐resistant and wild‐type lentiviral vectors. These PIs are candidates as new protease inhibitors effective against drug‐resistant HIV‐1.